Fabrication and performance investigation of 2-2 connectivity lead-free barium zirconate titanate-Portland cement composites - Potong R. (Elsevier Ltd, 2014)
The 2-2 connectivity lead-free barium zirconate titanate-Portland cement composites were fabricated by a dice-and-fill technique and designed for environmental friendly lead free piezoelectric materials. The 2-2 lead-free composites were also optimized from such aspects as volume content and composite connectivity. The theoretical equations of models were applied for the calculation with the dielectric constant, piezoelectric coefficient and piezoelectric voltage coefficient and the results were found to fit closest to that of the parallel model. The electromechanical coupling coefficient was found to increase with increasing BZT content from 18.7% to 22.5% when BZT volume content used was 30% and 70%. These composites were found to have higher piezoelectric voltage coefficient and lower acoustic impedance value than pure ceramic. Therefore, these composites have good compatibility with concrete structure and deemed suitable for use in smart concrete structures application. © 2014 Elsevier Ltd and Techna Group S.r.l.